Health Outcomes in Poor Countries and Policy Options : Empirical Findings from Demographic and Health Surveys - Wang, Limin (The World Bank, 2002)
Empirical studies on health at a disaggregate level—by socioeconomic group or geographic location—can provide useful information for designing poverty-focused interventions. Using Demographic and Health Survey (DHS) data, Wang investigates the determinants of health outcomes in low-income countries both at the national level, and for rural and urban areas separately. DHS data from more than 60 low-income countries between 1990 and 1999 reveal two interesting observations. First is the negative association between the level and inequality in child mortality. Second is the significant gap in child mortality between urban and rural areas, with the rural population having a much slower reduction in mortality compared with the urban population. Given that the poor are mainly concentrated in rural areas, the evidence suggests that health interventions implemented in the past decade may not have been as effective as intended in reaching the poor. The empirical findings in this study consolidate results from earlier studies and add new evidence. Wang finds that at the national level access to electricity, vaccination in the first year of life, and public health expenditure can significantly reduce child mortality. The electricity effect is shown to be independent of income. In urban areas only access to electricity has a significant health impact, while in rural areas increasing vaccination coverage is important for mortality reduction. This paper—a product of the Environment Department—is part of a larger effort in the department to better understand health-environment linkages. Please contact Limin Wang, room MC5-208, telephone 202-473-7596, fax 202-522-1735, email address lwang1@worldbank.org